Synthesis and NMR Spectral Data of some Esters Related to the Side Chains in Pluramycin Type Antibiotics - Heinz Nadig; Urs Séquin (CHIMIA)
Simple methyl esters can serve as suitable model compounds in the structural elucidation of the side chains in pluramycin type antibiotics. The 1H-NMR spectra of the model esters are in good agreement with those of the side chains of the corresponding antibiotics with respect to both, chemical shifts and coupling patterns, the former being consistently at lower fields for the natural products.